Recognizing pediatric febrile myoclonus: a video-documented case report and review of the current literature - Minerva, M.; Perilli, L.; Francioni, A.; Lotti, F.; Curcio, M. R.; Grosso, S. (Frontiers in Pediatrics, 2025)
Febrile myoclonus (FM) is a benign condition characterized by the sudden onset of generalized, multifocal, or segmental jerks during fever, without signs of central nervous system infections, resolving as the temperature elevation subsides. This condition is poorly described in literature, and its incidence is not well identified. We present the case of a 1-year-old child who developed myoclonic jerks during a febrile episode, diagnosed with FM. The child exhibited a normal neurological examination and neuromotor development appropriate for age. The electroencephalogram (EEG) showed no epileptiform discharges during the events, and past medical or familiar history was negative for epilepsy or any other neurological condition. We conducted a narrative review of the current literature to improve understanding of this benign clinical manifestation. Additionally, we included audio and video material to aid physicians in recognizing the condition, avoiding unnecessary diagnostic procedures and overtreatment with antiseizure medications. Our goal is to increase awareness of this rare phenomenon and expand its phenotypical spectrum.